Impact of cerebral hypoperfusion–reperfusion on optic nerve integrity and visual function in the DBA/2J mouse model of glaucoma. Issue 1 (14th September 2022) - Fraenkl, Stephan Alexander; Simon, Quentin; Yucel, Yeni; Gupta, Neeru; Wittwer, Valéry V; Frueh, Beatrice E; Tschanz, Stefan A
Abstract : Objective: One of the most important risk factors for developing a glaucomatous optic neuropathy is elevated intraocular pressure. Moreover, mechanisms such as altered perfusion have been postulated to injure the optical path. In a mouse model, we compare first negative effects of cerebral perfusion/reperfusion on the optic nerve structure versus alterations by elevated intraocular pressure. Second, we compare the alterations by isolated hypoperfusion-reperfusion and isolated intraocular pressure to the combination of both. Methods and analysis: Mice were divided in four groups: (1) controls; (2) perfusion altered mice that underwent transient bi-common carotid artery occlusion (BCCAO) for 40 min; (3) glaucoma group (DBA/2J mice); (4) combined glaucoma and altered perfusion (DBA/2J mice with transient BCCAO). Optic nerve sections were stereologically examined 10–12 weeks after intervention. Results: All experimental groups showed a decreased total axon number per optic nerve compared with controls. In DBA/2J and combined DBA/2J & BCCAO mice the significant decrease was roughly 50%, while BCCAO leaded to a 23% reduction of axon number, however reaching significance only in the direct t-test. The difference in axon number between BCCAO and both DBA/2J mice was almost 30%, lacking statistical significance due to a remarkably high variation in both DBA/2J groups. Conclusion: Elevated intraocular pressure in the DBA/2J mouse model of glaucoma leads to a much more pronounced optic nerve atrophy compared with transient forebrain hypoperfusion and reperfusion by BCCAO. A supposed worsening effect of an altered perfusion added to the pressure-related damage could not be detected.